Competitiveness of locations: the effects of regional innovation and entrepreneurial practices - Ferreira, João (2019)
The focus of this introduction article to the special issue is on the competitiveness of locations from an innovation and entrepreneurship perspective. The competitiveness of locations is a high potential research area as it combines economic geography, international business and regional economics. There is more emphasis on the competitiveness of a location because of the increased mobility of people and businesses to reside in their choice of location. [...]